Protego ergo obligo… Nuove forme di obbedienza per rinnovate forme di legittimità? (Altre Modernità, 2019)
This essay aims to analyse the relationship between work and legitimacy. This relationship is due to an increasing and pervasive expansion of the economic crisis that has significantly changed the relationship between state and citizen.